2011
DOI: 10.1016/j.amjcard.2011.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of β Blockers and Angiotensin-Converting Enzyme Inhibitors on Development of New-Onset Diabetes Mellitus in Patients With Stable Coronary Artery Disease

Abstract: We utilized data from patients with stable coronary artery disease (CAD) to assess the risk of new onset diabetes (NOD) with beta-blockers, and to determine whether angiotensin converting enzyme (ACE) inhibition would modify this risk. The Prevention of Events with Angiotensin Converting Enzyme Inhibition (PEACE) trial randomized 8290 patients with stable CAD to trandolapril or placebo. The presence of NOD was assessed at each study visit over a median follow-up time of 4.8 years. We examined the risk of NOD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…However, given the fact that there was marginal association between statin use and diabetes and the adherence to statin during outpatient follow-up was not properly evaluated, the association still remains uncertain in patients with coronary artery disease. In contrast to statin, we found an association of beta blocker use with new-onset diabetes consistent with previous studies in univariate analysis [ 8 , 33 ]; however, this association disappeared in multivariate analysis possibly due to more frequent use of beta blocker in AMI patients and the overwhelming diabetogenic effect of AMI compared with beta blocker use in multivariate analysis.…”
Section: Discussionsupporting
confidence: 90%
“…However, given the fact that there was marginal association between statin use and diabetes and the adherence to statin during outpatient follow-up was not properly evaluated, the association still remains uncertain in patients with coronary artery disease. In contrast to statin, we found an association of beta blocker use with new-onset diabetes consistent with previous studies in univariate analysis [ 8 , 33 ]; however, this association disappeared in multivariate analysis possibly due to more frequent use of beta blocker in AMI patients and the overwhelming diabetogenic effect of AMI compared with beta blocker use in multivariate analysis.…”
Section: Discussionsupporting
confidence: 90%
“…It seems that the predictive role of RHR in patients on beta-blocker treatment is greater (HR, 1.19; 95% CI, 1.04-1.37) than those without beta-blocker use (HR, 1.03 95% CI, 0.90-1.18), although this was not statistically significant. This is not surprising considering the fact that beta-blockers favor insulin resistance and increase the risk of developing diabetes (39).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was reported that diabetes may be prevented by renin–angiotensin blockers . Recently, a number of trials on antihypertensive medications such as angiotensin‐converting enzyme inhibitors (ACEIs), ARBs, CCBs, diuretics and β‐blockers have explored whether these medications influenced NOD development .…”
Section: Introductionmentioning
confidence: 99%
“…CCB could significantly reduce the incidence of NOD, and CCB combined with ARB had metabolically neutral effects . Effects of β‐blockers on NOD patient are controversial which might contribute to a reduced mortality and morbidity of heart failure among patients with NOD , while it might trigger the development of NOD . It was also indicated that the use of diuretic is associated with a decreased incidence of NOD and prolonged diuretic treatment may result in an increased fasting glucose .…”
Section: Introductionmentioning
confidence: 99%